Constituição para que(m)? - Maurício Sullivan Balhe Guedes (2020)
The Brazilian doctrine of effectiveness branded the past as insincere or unimportant, and in its attempt to overcome it, instituted in the 1988 Constitution a radical model of legal constitutionalism with strong concentration on the figure of the Federal Supreme Court. The essay develops a counternarrative that seeks to deconstruct the “myth of normative insincerity” and affirms that the doctrine of effectiveness has constructed an incorrect representation of the country's historiographical reality. The reconstruction of the traditions of the brazilian constitutionalism demonstrates that all have achieved and, in some way, still take place in theideals and legal life. In the end, it explores the problem of efficacy and legitimacy in legal constitutionalism and demonstrates that, if it does not recognize the importance of history, it will be the doctrine of effectiveness to repeat the myth it has constructed.